Letter - Chapman, Caroline
037-0018-001 DUNDEE BASQUE CHILDREN'S COMMITTEE Convener: Mr A.R. DAW, 17 Harefield Avenue. Treasurer: Rev. A. WHITFORD, 42 Albany Terrace. Secretary: Mrs C. CHAPMAN, B.A. (Lond.). 94 Ellengowan Drive. HOME FOR BASQUE CHILDREN at Mall Park House, Montrose. Matron: Miss M. WILSON Ref. HVT/FC/EW/86. 94, Ellengowan Drive, Dundee. Nov. 26th, 1937. H.V. Tewson Esq. Representative of Trades Union Congress on Basque Children's Committee. Sir, With reference to your letter of July 6th, I have to inform you that a Dundee Branch of the Basque Children's Committee was formed at a public meeting held on July 9th, for the purpose of setting up a Scottish Basque Refugee Home. On the Committee are represented the Dundee Spanish Medical Aid Committee, the Perth Trades and Industrial Council, the Montrose Co-operative Society, the Dundee Presbytery and Methodist Church. It arranged for 24 Basque children to come to Scotland from the camp at Southampton, on Sept. 17th, and established them in a Home at Montrose, for which it has accepted full financial responsibility. We are therefore appealing to all organisations in Scotland working for Spanish Relief, to help support the only Basque Refugee Home in Scotland. On approaching the Dundee Trades and Labour Council for support, we were told that they were already contributing to the National Labour Party Solidarity Fund for Basque Children.(some £3 per week). We then applied to the central Basque Children's Committee to have this contribution set aside for the Scottish Home at Montrose, but were informed that they were not receiving it, that it was paid to the Trades Union Congress. Will you help us by raising the matter with the Trades Union Congress, and asking that the Dundee contribution be given to the Scottish Refugee Home at Montrose ? I am, Yours faithfully, Caroline Chapman Hon. Sec. Dundee Basque Children's Cttee. 292/946/37/18